(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
The essay reconstructs the complex and often conflictual relationships between Ugo Foscolo and his publishers, printers, and editorial collaborators, examining how these dynamics influenced the production and reception of his works. Through the analysis of key episodes – such as the publication of Sepolcri, the translation of Sterne’s A Sentimental Journey, tensions with Nicolò Bettoni, and his involvement in journalism –are here highlighted the many roles Foscolo assumed: author, translator, reviser, editor, and even promoter of his own writings. The article offers a reflection on Foscolo’s conception of literature and his almost obsessive attention to the editorial form of his texts, suggesting that his practices anticipated a modern model of the “author’s edition.”